Birthspacing and fertility decline in Costa Rica - Víctor Gómez (Población y Salud en Mesoamérica)
This paper uses data from the Latin American Comparative Fertility Surveys as well as from the World Fertility Survey to study trends and differentials in birthspacing among ever married women in Costa Rica during the period 1945-1974. A good deal of attention is placed on the pace of fertility in threshold, early and late stages of the fertility decline that this country experienced during the sixties and early seventies. The results show a good deal of similarity in the tempo of reproduction across parities and geographical areas. However, an analysis of the background variables affecting birthspacing shows differences between urban and rural zones. Finally, it is postulated that the recent plateau in period rates may be a consequence of changes in the tempo of family building, with women at low parities having their postponed births now, offsetting the trends of decline generated among women at higher parities who still may be curtailing reproduction.